TEACHING READING COMPREHENSION THROUGH COMPENSATION STRATEGY TO THE EIGHTH GRADE STUDENTS’ OF SMP 4 KEJURUAN MUDA - Chairuddin Chairuddin (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
This research was aimed at finding out the significant contribution of teaching reading comprehension through Compensation strategy to the eighth grade students’ achievement at SMP N 4 Kejuruan Muda. This research employed a quantitative research design in particular Classroom Action Research. The data were obtained by using some instruments. Among of them are: 1) Test (consisting pre-test and post-test), 2) Classroom observation (including treatment), and 3) Interview (involving the English teachers). The result of the research revealed that teaching reading comprehension through Compensation strategy showed significant effect to the eighth grade students’ achievement at SMP N 4 Kejuruan Muda by comparing the test result in the two cycles, in which the mean in cycle I was 56,7 and in cycle II was 67,00